PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA KFC DI KOTA BENGKULU - Yudi Irawan Abi (Management Insight: Jurnal Ilmiah Manajemen, 2020)
The purpose of this study is to look at the effect of brand image and product quality on purchasing decisions for KFC products in the city of Bengkulu. This research was conducted based on a quantitative approach. Data were collected using a questionnaire involving 100 respondents. Data analysis was used using multiple linear regression. The results of this study reveal that the influence of brand image has a significant effect on purchasing decisions on KFC products in Bengkulu City. The effect of product quality has a significant effect on decisions on KFC products in Bengkulu City.Keywords: product quality; Product Knowledge; and Purchase Decision.